HLA class II allele genetic propensity in Oral submucous fibrosis - Dr Bharathi M Purohit; Dr Uma Kanga; Dr Harsh Priya; Prof Ritu Duggal; Dr Shalini Gupta (Elsevier, 2023)
Aim or Purpose: Oral Sub-Mucous Fibrosis (OSMF) is a premalignant condition that alters fibro elasticity of oral submucosa and predominantly confined to Southeast Asian region. Variability in clinical course is intriguing, a fraction of betel nut users develops OSMF (0.1-11%), while a majority show no signs and symptoms despite prolonged use; severe forms are associated with very short history of tobacco use. This inconsistency in disease association is indicative of genetic association, but specific role of genes in its susceptibility remains largely unidentified. The objective was to assess and compare HLA-DRB1, -DQB1, -DPB1 allele phenotype frequencies in OSMF patients and healthy controls. Materials and Methods: Patients aged 18-55 years were recruited and tobacco history was recorded followed by collection of blood sample for DNA extraction and quality check. HLA class II genotyping was performed using Next Generation Sequencing protocol for 154 samples with 119 OSMF patients and 35 controls. Data was analysed using sequencing software. Study was approved by Institute Ethics committee of AIIMS New Delhi and study duration was 18 months. Results: Mean age of patients was 42.23±11.98 years with mild (36.7%), moderate (36.7%) and severe (26.7%) OSMF patients. -DPB1*04 was observed as the most frequent allele (71.43%) followed by HLA-DQB1 *03 allele in 46.5% of the samples. HLA-DQB1 *04 was the least frequent allele present in 1.73% of the samples. Conclusions: Insights into potential predisposing or protective HLA allele help better characterize inter individual variations in immune responses in severity and progression of OSMF and develop potential genetic biomarker for screening and prognosis & reduce malignant transformation rate in OSMF.